2005
DOI: 10.1152/ajpheart.00739.2004
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a functional calcium-sensing receptor that modulates myogenic tone in rat subcutaneous small arteries

Abstract: ), and, recently, a receptor that senses changes in Ca 2ϩ , the calcium-sensing receptor (CaR), has been detected in vascular tissue. We investigated whether the CaR is involved in the regulation of myogenic tone in rat subcutaneous small arteries. Immunoblot analysis using a monoclonal antibody against the CaR demonstrated its presence in rat subcutaneous arteries. To determine whether the CaR was functionally active, segments of artery (Ͻ250 m internal diameter) mounted in a pressure myograph with an intralu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
65
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 49 publications
6
65
0
1
Order By: Relevance
“…This is compatible with a compensatory increase in HR in response to a decrease of BP induced by vasodilation of resistance arteries. The CaR is expressed in a wide variety of rat small arteries, including renal, mesenteric, cerebral, and subcutaneous vessels (11)(12)(13). It has been localized in adventitial perivascular nerves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is compatible with a compensatory increase in HR in response to a decrease of BP induced by vasodilation of resistance arteries. The CaR is expressed in a wide variety of rat small arteries, including renal, mesenteric, cerebral, and subcutaneous vessels (11)(12)(13). It has been localized in adventitial perivascular nerves.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the CaR by a progressive increase in ambient calcium results in a U-shaped response with constriction at medium calcium concentrations and marked vasodilation at high and low calcium concentrations. The known agonists magnesium and aminoglycosides induce dose-dependent vascular (11); the neuronally released vasodilator substance is a cannabinoid receptor agonist (14). Accordingly, R-568 may result in reduced peripheral vascular resistance in the rat model, either directly via activation of the CaR or indirectly by the decrease of ionized calcium to subnormal levels.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have reported that the CaR is expressed in many cardiovascular tissues, including human aortic endothelial cells (Ziegelstein et al 2006), rat cardiomyocytes (Tfelt-Hansen et al 2006) and is also present in rat s.c. small arteries (Ohanian et al 2005). Therefore, the influence of calcilytic on blood pressure is not excluded.…”
Section: Discussionmentioning
confidence: 99%
“…The most valuable explanation is related to the control of PTH levels without increasing the Ca ϫ P. Lopez et al (49), in addition, pointed to a direct action of calcimimetic at the cellular level on the arterial wall. Vessels express CaR (50), and some investigators have demonstrated the presence of CaR using a polyclonal antibody to the CaR (51), whereas other preliminary studies have failed to detect CaR in bovine and human VSMC using RNase protection assays (52). Calcium modulates the function of vessels, and it is of considerable importance the findings that calcimimetics influence BP profile.…”
Section: Cinacalcet and Vcmentioning
confidence: 99%